MELD at POD 1 as a predictor of outcome in liver allografts with peak AST >5000 U/l. (29th September 2014) - Hoyer, Dieter P.; Sotiropoulos, Georgios C.; Saner, Fuat H.; Treckmann, Jürgen W.; Paul, Andreas; Mathé, Zoltan
Summary Perioperative liver graft injury is associated with elevation of aminotransferases after orthotopic liver transplantation (OLT). Values above 5000 U/l usually are regarded as extreme liver graft injury (ELGI). Some patients and organs recover from this critical condition. The aim of the study was to evaluate factors contributing to graft and patient survival after ELGI. From chart review we identified 64 of 917 OLT adult patients (median age 54.2 years; 68.8% males) transplanted between 11/2003 and 02/2012, who presented ELGI after OLT. Donor and recipient factors were analyzed and correlated with the outcome by univariable and multivariable methods. Multivariable cox proportional hazards showed that recipient's BMI (P = 0.01), model for end stage liver disease (MELD) score before OLT (P = 0.02) and laboratory MELD score 24 h after OLT (P = 0.01) were independently associated with patient survival. 30‐days and 12‐months survival in patients with a postoperative laboratory MELD higher than 31 was 21.4%, while patients with a postoperative laboratory MELD lower than 31 displayed 30‐days and 12‐months survival rates of 80% and 71.8%, respectively (P < 0.001). Retransplantation in the setting of ELGI after OLT should be based on all available data. Utilization of the postoperative labMELD enables the transplant physician within 24 h after transplantation to identify necessity of retransplantation objectively.